Relationship between impulsivity levels and social media addiction in health services vocational school students - Topbaş, Zehra Su; Karakay, Arzu (Journal of Dependence, 2021)
Objective: The aim of this study is to examine the relationship between impulsivity levels of university students and social media addiction and the difference between impulsivity and social media addiction according to gender variable.Method: The correlation design of the quantitative research method was used. The study was conducted with 306 students studying at a health services vocational school. Sociodemographic Data Collection Forum, Short Form of Barratt Impulsiveness Scale (BIS-11-SF) and Social Media Addiction Scale-Adult Form were used to collect data.Results: As a result of statistical analysis, it was seen that there was a positive significant relationship between impulsivity level and social media addiction scores, and it was found that the impulsivity variable explained 18% of the total variance (R = .18, p = .00). It was observed that there was no significant difference in the impulsivity level and social media addiction of women and men.Conclusion: In this sample of Health Services Vocational School students, impulsivity predicts social media addiction.
Keywords: Social media; social networking; addiction; addictive behavior